The shoe : Best Foot Forward - Blanchard, Tamsin (London Carlton Books, 2012)
Statistics show that the average woman owns 20 pairs of shoes and more than half of them are never worn. Some own as many as 100 pairs. This title reveals facts about the craftsmanship behind the industry as well as profiles on the world's most coveted and iconic designer brands thorough over 200 images of the shoes.
Include coloure illustrations and index
Keywords: a